Girl Students' Attitude towards Yoga in the Public Campuses of Kathmandu and Rautahat Districts in Nepal (Interdisciplinary Research in Education, 2023)
This article aims to find out and compare the attitude towards yoga among girl students in the public campuses of Kathmandu and Rautahat districts. A comparative descriptive study including multistage (convenient, census and simple random) sampling methods was done among the total 60 respondent students from two campuses of Kathmandu and one campus from Rautahat. An interview schedule including ten statements (five positive and five negative statements) in a five-point Likert scale format was used as the tool. The attitudes’ score of the students of Kathmandu was found better in all aspects than Rautahat. Total respondents of both districts had shown favorable scores i.e. obtained score > neutral score (1286 and 1065 > 900) or had positive attitude towards yoga. There was a significant difference on attitude towards yoga between the girls of both districts. The supporting variables in Kathmandu, i.e. positive gender feeling, leisure time, information, teachers’ factor, yoga proficiency, social belief, home and campus environment than in Rautahat, are indicated as role player in creating the difference in the attitudes of the girls.